Can Policies Affect Employment Intensity of Growth? : A Cross-Country Analysis - Furceri, Davide (IMF Working Papers; Working Paper ;, 2012)
The aim of this paper is to provide new estimates of employment-output elasticities and assess the effect of structural and macroeocnomic policies on the employment-intensity of growth. Using an unbalanced panel of 167 countries over the period 1991 - 2009, the results suggest that structural policies aimed at increasing labor and product market flexibility and reducing government size have a significant and positive impact on employment elasticities. In addition, the results also suggest that in order to maximize the positive impact on the responsiveness of employment to economic activity, structural policies have to be complemented with macroeconomic policies aimed at increasing macroeconomic stability.